Notes on typography for native languages of Brazil - Diniz, Kollontai Cossich (InfoDesign, 2007)
The aim of this research is sharing questionings aroused from the analysis of typographical projects of publications in Brazilian indigenous languages. We trace an overview of the indigenous populations uses of writing and point our doubts concerning what would be an appropriate typography for this use, suggesting some answers, with the special intention of alerting the Brazilian typography community of the necessity and urgency of being sensitive to the social demands that surrounds us.